Aleutian disease in ferrets. - Porter, H G (1982)
When 32 antibody-free ferrets were inoculated with the highly mink-virulent Utah-1 strain of Aleutian disease virus (ADV), most developed ADV antibody starting 15 days after infection, but the antibody titers were much lower than those seen in mink. Relatively small amounts of ADV were demonstrated in CRFK cell culture, using ferret spleen and lymph node homogenates only 4 to 10 days after experimental infection, but low-level viral persistence for 180 days was shown by mink inoculation. The ferrets inoculated with the Utah-1 strain of ADV did not develop elevated gamma globulin levels, but did have mild tissue lesions. Forty-two percent of a group of 214, approximately 1-year-old, recently pregnant, female ferrets were found to have antibody to ADV. An analysis of the serum proteins of the ferrets with ADV antibody showed that they had a significant, but mild, elevation of their serum gamma globulin. Serial ferret-to-ferret transmission of a ferret strain of ADV by inoculation of spleen homogenates was demonstrated, and some of these ferrets developed liver lesions. Mink inoculated with ferret ADV made antibody, but did not develop hypergammaglobulinemia or tissue lesions. Although both ferret and mink strains of ADV replicate and persist in the ferret, they fail to cause severe disease of the type usually seen in the closely related mink. Mink and ferret ADV strains appear to be biologically distinct.